2021
DOI: 10.1128/mbio.01566-21
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Streptomyces hygroscopicus OsiSh-2-Mediated Balancing between Growth and Disease Resistance in Host Rice

Abstract: Under disease stress, activation of defense response in plants often comes with the cost of a reduction in growth and yield, which is referred as the growth-defense trade-off. The microorganisms which can be recruited by plants to mitigate the growth-defense trade-off are of great value in crop breeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…As our previous study showed that OsiSh-2 inoculation could induce host resistance to rice blast while still maintaining high growth, 29 we also investigated the growth of rice under M. oryzae stress. Consistent with the previous results, the total chlorophyll content in E+ rice was significantly increased by 33.3% compared with that in E− rice under M. oryzae infection (Figure 8C).…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As our previous study showed that OsiSh-2 inoculation could induce host resistance to rice blast while still maintaining high growth, 29 we also investigated the growth of rice under M. oryzae stress. Consistent with the previous results, the total chlorophyll content in E+ rice was significantly increased by 33.3% compared with that in E− rice under M. oryzae infection (Figure 8C).…”
Section: ■ Resultsmentioning
confidence: 99%
“…However, the WT strain showed cellular homeostasis with the host rice and maintained a balance of growth and defense. 29 The WT strain without growth defects required less biomass to reach this symbiotic status with the host, thus explaining why the biomass of WT was lower than that of ΔTHIC in rice. In addition, since WT could provide thiamine to rice, the rice could utilize the energy saved by reducing thiamine synthetic levels to maintain an active growth status, even during M. oryzae invasion (Figure 8C−G).…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain PRh5 [48], Streptomyces sp. 11-1-2 [29,49], S. hygroscopicus Osish-2 [50][51][52][53][54], Streptomyces sp. NBRC 109436 [55] and S. rhizosphaericus NRRL B-24304 [32] were isolated from the rhizosphere of diverse plants across the world.…”
Section: Chromosome-scale Assembly Of Agn23 and Genome-based Taxonomi...mentioning
confidence: 99%
“…Compared with soil microorganisms, endophytes within plants may have more positive and direct impacts on plants because of their special ecological niches. The results from different research teams have provided good evidence for the effects of endophytes on plant growth promotion, stress mitigation, and disease resistance in host plants [ 9 , 10 , 11 , 12 ]. The mechanisms proposed for disease prevention include competition with pathogens for niche and nutrition, induction of plant resistance, secretion of bioactive metabolites, and promotion of plant growth, usually working in concert [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%